Ethics, Representation, and a “Filipino Ecocriticism” of Yolanda in Daryll Delgado’s Remains - Mylene C. Milan (Asiatic: IIUM Journal of English Language and Literature, 2026)
Even over a decade since super typhoon Haiyan (known as Yolanda in the Philippines) struck central Visayan regions of the archipelago, survivors continue recalling their mortifying experiences at the mention of the storm. However, literature continuously flourished to keep the memory not only of the destruction but also of the survival and resilience that surrounded its aftermath. Jeffrey Santa Ana regards this literary intelligence as a “Filipino ecocriticism,” which discloses how historical violence aggravated weather events across the Philippines and the Southeast Asian region. Using this lens in the close reading of Daryll Delgado’s novel Remains (2019), this article intersects issues of ethics and fictionality on the representation of real-life experiences in the wake of the most devastating land-falling storm in modern Philippine meteorology. It draws insights on postcolonialism, positionality, and ethical witnessing from the works of Sarita See, Walter Benjamin, Jocelyn S. Martin, and an online interview with the author herself. Towards the end, this article ultimately discloses “literarising truths” as a non-neutral approach on the sociopolitical realities that lies at the core of representing climate disasters.